Co-optimising renewable expansion and long-duration storage for a high-density island power system: Pathway for Taiwan (2025–2050) - Mohamed Shaaban (Results in Engineering)
Achieving Taiwan’s legally mandated net-zero target by 2050 requires rapid scale-up of renewable energy and long-duration storage within the constraints of a densely populated island grid. This study presents an integrated capacity-expansion and hourly unit-commitment model that co-optimises generation, storage and transmission across six regional zones from 2025 to 2050. Scenario analysis couples technology-specific cost trajectories with carbon-pricing pathways to quantify least-cost portfolios capable of meeting reliability and emissions constraints. Results show that offshore wind and rooftop PV can supply 73 % of electricity in 2035 and 88 % by 2050 when supported by 9 GW of pumped-hydro and 24 GWh of lithium-ion storage, reducing power-sector CO₂ emissions by 98 % relative to 2025. Sensitivity tests reveal that hydrogen storage becomes competitive only if electrolyser costs fall below 300 $ kW⁻¹ or carbon prices exceed 150 $ tCO₂⁻¹. System-level levelised cost of electricity rises modestly from 110 to 124 $ MWh⁻¹ by 2050 less than half the cost of unabated fossil backup while loss-of-load probability remains below 0.05 %. Comparative analysis with other high-density coastal systems underscores the critical role of Taiwan’s mountainous pumped-hydro reservoirs in providing seasonal balancing. Policy implications include phasing out coal by 2040, streamlining offshore wind permitting and prioritising hybrid battery-hydrogen storage hubs near load centres.